Perceived Epistemic Risk as a Costly Signal of Credibility Among Educational Influencers in Indonesia - Ferry Irwandi; Diyah Pujiastuti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Digital educational discourse is increasingly saturated with “cheap talk,” driven by an information economy where misinformation is easy to produce, making trust scarce. To address this issue, this study applies the Handicap Principle in Indonesia’s digital context through a new concept: Perceived Epistemic Risk (PER). It argues that influencers who willingly face legal risks—such as under the Personal Data Protection Law (UU PDP)—and social backlash send a “costly signal” of honesty that is difficult to fake. Using data from 300 followers of high-risk educational influencers and analyzed with PLS-SEM, the study finds a strong positive relationship between PER and Source Credibility. This relationship is fully mediated by Perceived Authenticity (PASMI). The findings challenge traditional credibility models, showing that in a high-risk digital environment, audiences interpret “danger” as a sign of expertise rather than a deterrent. Ultimately, legal vulnerability becomes a key marker distinguishing genuinely credible influencers from opportunistic content creators.